Applying incremental Deep Neural Networks-based posture recognition model for ergonomics risk assessment in construction. (October 2021) - Zhao, Junqi; Obonyo, Esther
Highlights: Monitoring and assessing awkward postures help to prevent injuries in construction. Incremental DNN-based recognition models can continuously learn new postures. Incremental models can keep the memory of learned postures after adaptation. Ergonomics assessment with recognized and actual postures shows comparable results. Abstract: Monitoring and assessing awkward postures is a proactive approach for Musculoskeletal Disorders (MSDs) prevention in construction. Machine Learning models have shown promising results when used in recognition of workers' posture from Wearable Sensors. However, there is a need to further investigate: i) how to enable Incremental Learning, where trained recognition models continuously learn new postures from incoming subjects while controlling the forgetting of learned postures; ii) the validity of ergonomics risk assessment with recognized postures. The research discussed in this paper seeks to address this need through an adaptive posture recognition model– the incremental Convolutional Long Short-Term Memory (CLN) model. The paper discusses the methodology used to develop and validate this model's use as an effective Incremental Learning strategy. The evaluation was based on real construction workers' natural postures during their daily tasks. The CLN model with "shallow" (up to two) convolutional layers achieved high recognition performance (Macro F1 Score) under personalized (0.87) and generalized (0.84) modeling. Generalized CLN model, with one convolutional layer, using the "Many-to-One" Incremental Learning scheme can potentially balance the performance of adaptation and controlling forgetting. Applying the ergonomics rules on recognized and ground truth postures yielded comparable risk assessment results. These findings support that the proposed incremental Deep Neural Networks model has a high potential for adaptive posture recognition. They can be deployed alongside ergonomics rules for effective MSDs risk assessment.